PERFORMA KUALITATIF DAN KUANTITATIF AYAM KAMPUNG (Gallus Gallus Domesticus) DI PETERNAKAN PEMBIBITAN THE MOTHER - Riyanti Riyanti; Khaira Nova; Teguh Rafian; Sulastri Sulastri; Adityo Suhadi; Mentari Mentari (Wahana Peternakan, 2023)
This study aims to identify the quantitative and qualitative performance of native chickens in The Mother breeding farm. This study used 50 male native chickens and 50 female native chickens aged 7 months. Variables observed included body hair pattern color, comb shape, comb color, shank color, eye color, beak color, body weight, chest circumference, shank length, shank circumference, body length, pubic bone length to chest, pubic bone distance and length wing span. Data were analyzed using descriptive analysis. The results of this study indicate that the body color of the male is Columbian (100%), while the female is solid black (62%), columbian (22%) and speckled or dotted (16%). The male cockscomb is pea (86%) and single (14%), while the female is pea (70%), walnut (20%) and single (10%). The color of the male comb is red (100%), while the female is red (98%) and black (2%). The shank color of males is yellow (74%), black (14%) and white (12%), females are black (74%), white (16%) and yellow (10%). Male eye color is orange (76%) and yellow (24%), while females are orange (66%), yellow (20%) and brown (14%). The color of the male's beak is yellow (54%), black and yellow (38%) and white (8%), while the female's beak is black and yellow (82%), yellow (10%) and white (8%). The results of the quantitative characteristics of the study showed that the male body weight was 2.22 ± 2.02 kg and the female was 1.71 ± 0.25 kg, the male chest circumference was 33.9 ± 3.68 cm and the female was 30.67 ± 2.08 cm, the length male shank 9.61 ± 0.89 cm and female 27 ± 0.59 cm, male shank circumference 5.52 ± 0.65 cm and female 4.4 ± 0.5 cm, male body length 20.27 ± 1.17 cm and female 20.40 ± 2.27 cm, the length of the pubic bone to the chest of the female is 7.87 ± 1.06 cm, the distance between the pubic bones is 2.8 ± 0.49 cm, the length of the male wing span is 23.28 ±2.18 cm and females 16.61±2.44 cm. The conclusion of this study is that the quantitative and qualitative characteristics of free-range chickens on The Mother farm are diverse and selection can be made. Keywords: Domestication chicken, Selection, Quality breeds, Lampung Province